THE THE EFFECT OF Glomus deserticola ON THE MANAGEMENT OF Alectra vogelii IN COWPEA (Vigna unguiculata L. Walp) VARIETIES - Makanjuola, Deborah O.; Alonge, Samson O.; Ibrahim, Azeezat A.; Ariyo, Olalekan I.; Anayochukwu, Christie A. (FUDMA JOURNAL OF SCIENCES, 2025)
This research was conducted to evaluate the effect of Glomus deserticola on the management of root and shoot dry weight of four cowpea varieties in an Alectra vogelii inoculated soil. The four cowpea varieties used were: SAMPEA 7, IFE 82-12, IT97K-499-35 and TVX 3236. The sterilized sandy-loamy soil used for this experiment consisted of mixture of top soil and sand in ratio 1:1 (v/v). Glomus deserticola treatments was applied at five rates: the zero and without Alectra, zero and with Alectra, 10, 20 and 30 g/pot each with Alectra. A constant quantity of Alectra (3.3 g) was maintained where applicable. The treatments were arranged in complete randomized design. The cowpea plants were sampled for root and shoot dry weight at 5, 7 and 9 weeks after planting (WAP). The ANOVA of the three years data showed that Glomus deserticola treatments at different rates significantly increased cowpea root and shoot dry weights compared with the control treatments. Glomus deserticola at 30 g/pot resulted in the highest root and shoot dry weight of the cowpea varieties. SAMPEA 7 treated with Glomus deserticola, had higher values of root and shoot dry weight than the other cowpea varieties at 9 WAP. In conclusion, Glomus deserticola treatments significantly increased root and shoot dry weight of the four cowpea varieties on Alectra inoculated soil and can be recommended as a biological control agent in Alectra vogelii infested fields.